Scientology : the science of truth or the art of deception? - Fromm, Rainer, 1965-; Matthias-Film (Firm); Soundview Media Partners ([Berlin, Germany] : Matthias-Film gGmbH, 2009)
To some, Scientology is a bona fide religion based upon rigorous research with doctrines akin to universal scientific laws. To others, including some former members, Scientology is a cult with so-called doctrines that are nothing more than ridiculous science-fiction stories invented by founder L. Ron Hubbard. Although Scientology is controversial, it is recognized as a legitimate tax-exempt religious organization in the U.S. and in many other countries. However, countries including Great Britain, France, and Germany refuse to grant such status, citing evidence that Scientology's tenets are diametrically opposed to the values of democratic societies.
Originally released as a motion picture in 2009.
Camera, Michelle Mèuhlenbruch-Bunn ; editors, Sebastian Kerz, Anina Wolf ; music, Unternehmen Stahlklang.
In English and German; with English translation of German speakers.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 30, 2020)
Keywords: Scientology; Cults; Documentary films; Feature films; Nonfiction films; Internet videos; Streaming video